Barriers influencing participation on Employee Health and Wellness Programmes at Seshego One-Stop Centre, Polokwane Sub-District, Limpopo Province - Maluleke, Tumelo Faith (My University, 2021)
The study was conducted in Polokwane sub-district targeting all the employees at Polokwane One-stop Centre. The specific focus was drawn to all permanent Social workers, Community Development workers and Social Auxiliary workers. The aim of the study was to explore barriers influencing employee participation in Employee Health and Wellness Programmes and to describe barriers influencing employee participation in Employee Health and Wellness Programmes. The data was collected through semi-structured face-to-face interview from all employees who are employed by the Department of Social Development, Polokwane Sub-District. The sample consisted of permanent Social workers, community development workers and social auxiliary workers who have more than one year of experience in the department of social development and excluded all employees who were on the internship programme. The researcher used thematic data analysis to analyse the findings of the study. The study concluded that employees were not participating in the EHWP because of limited knowledge of services rendered at the EHW programme, lack of access to EHW services, privacy and confidentiality of service providers and expertise knowledge of those offering the programmes and inadequate support from management. It is recommended that those in leadership should ensure that they disseminate information about EHWP to all employees.
Thesis (MPH.) -- University of Limpopo, 2021
Keywords: Barriers; Employee health and wellness programme,; Employees; Wellness; Employee health promotion; Government employees